THE ROLE OF CODE-SWITCHING IN MULTILINGUAL CLASSROOMS - Yusupov Asadbek G‘afur o‘g‘li (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotatsiya: This study investigates the role of code-switching in multilingual classrooms, focusing on secondary schools in Uzbekistan where Uzbek, Russian, and English are used. Using qualitative methods, including classroom observations and interviews with teachers and students, the research explores how code-switching functions as a communicative and pedagogical tool. The findings reveal that code-switching facilitates comprehension, social interaction, and reduces learner anxiety, although excessive use may limit target language exposure. The study concludes that strategic use of code-switching enhances language learning and recommends incorporating it thoughtfully into teaching practices.